Prophetic Leadership as an Effort to Plant Moderate Value of Santri - Muhammad Amin Fathih; Triyo Supriyatno; M. Fahim Tharaba (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
The radicalism movement has become the main cause of the growth of terrorism cases in Indonesia. This movement has successfully spread to various educational institutions, one of which is pesantren (Islamic boarding schools). The entry of radicalism into pesantren is inseparable from the lack of internalization of religious moderation attitudes by pesantren leaders towards their students. The Kiai, through a prophetic leadership model, have a major role in internalizing religious moderation in their students through their influence in pesantren. This research aims to find the concept of prophetic leadership, prophetic leadership strategies in internalizing religious moderation, and the implications of prophetic leadership. This research uses a qualitative approach with a multisite study type. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis uses data condensation, data display, and making conclusions. The research results conclude that the concept of prophetic leadership is carried out through education, religious learning, and istiqamah (steadfastness) in worship. The strategy of internalizing religious moderation is carried out by exemplification, habituation, and understanding. The implications of prophetic leadership include strengthening the religious moderation of students, strengthening moderation education, and forming student morals.